Analysis of the functions of TaGW2 homoeologs in wheat grain weight and protein content traits - Zhang, Yi; Li, Da; Zhang, Dingbo; Zhao, Xiaoge; Cao, Xuemin; Dong, Lingli; Liu, Jinxing; Chen, Kunling; Zhang, Huawei; Gao, Caixia; Wang, Daowen (The Plant journal : for cell and molecular biology, 2018)
Summary GW2 is emerging as a key genetic determinant of grain weight in cereal crops; it has three homoeologs (TaGW2‐A1, ‐B1 and ‐D1) in hexaploid common wheat (Triticum aestivum L.). Here, by analyzing the gene editing mutants that lack one (B1 or D1), two (B1 and D1) or all three (A1, B1 and D1) homoeologs of TaGW2, several insights are gained into the functions of TaGW2‐B1 and ‐D1 in common wheat grain traits. First, both TaGW2‐B1 and ‐D1 affect thousand‐grain weight (TGW) by influencing grain width and length, but the effect conferred by TaGW2‐B1 is stronger than that of TaGW2‐D1. Second, there exists functional interaction between TaGW2 homoeologs because the TGW increase shown by a double mutant (lacking B1 and D1) was substantially larger than that of their single mutants. Third, both TaGW2‐B1 and ‐D1 modulate cell number and length in the outer pericarp of developing grains, with TaGW2‐B1 being more potent. Finally, TaGW2 homoeologs also affect grain protein content as this parameter was generally increased in the mutants, especially in the lines lacking two or three homoeologs. Consistent with this finding, two wheat end‐use quality‐related parameters, flour protein content and gluten strength, were considerably elevated in the mutants. Collectively, our data shed light on functional difference between and additive interaction of TaGW2 homoeologs in the genetic control of grain weight and protein content traits in common wheat, which may accelerate further research on this important gene and its application in wheat improvement. Significance Statement GW2 is emerging as a key determinant of grain weight in cereal crops. Here, we revealed the function of two homoeologs of TaGW2 (TaGW2‐B1 and ‐D1) in the genetic control of common wheat grain weight via modulating maternal pericarp cell growth. The two homoeologs also affected grain protein content. Our data should stimulate further functional and applied studies on TaGW2.